2021
DOI: 10.1364/ao.420857
|View full text |Cite
|
Sign up to set email alerts
|

Polarization property associated with surface plasmon resonance in a metal grating in a conical mounting and its application to refractive index sensing

Abstract: We focus on the normalized Stokes parameter s 3 of the specularly reflected light from a metal grating in a conical mounting in order to accurately and sensitively detect the occurrence of surface plasmon resonance (SPR). Experimental and theoretical investigations into the incident angle dependence of s 3 reveal a rapid change in s 3 around the resonance angle θ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The curve shows the partial absorption of the incidental light as a dip in the vicinity of and rapidly fluctuates between a positive maximum value and a negative minimum value via zero at . The rapid change in as well as the absorption dip of is caused by the occurrence of SPR [ 23 ]. The SPR of in the bare Al portion is associated with the coupling of the TM component in the −1st-order evanescent mode with the surface plasmon wave propagating along the surface of the aluminum grating [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The curve shows the partial absorption of the incidental light as a dip in the vicinity of and rapidly fluctuates between a positive maximum value and a negative minimum value via zero at . The rapid change in as well as the absorption dip of is caused by the occurrence of SPR [ 23 ]. The SPR of in the bare Al portion is associated with the coupling of the TM component in the −1st-order evanescent mode with the surface plasmon wave propagating along the surface of the aluminum grating [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…We examined a metal diffraction grating coated with a Pd thin-film which served as a coupler to excite surface plasmons and a transducer to convert hydrogen exposure to a change in its complex refractive index. We have observed that UV holographic aluminum gratings from Edmund Optics, Inc., Tokyo, Japan which have a shallow groove depth of several tens of nanometers, exhibit sharp SPR characteristics [ 23 , 26 ]. In this study, we used a UV holographic aluminum grating, with a groove density of 2400 lines/mm (Edmund Optics, Inc., stock no.…”
Section: Preparation For Experimentsmentioning
confidence: 99%
See 3 more Smart Citations